Pathways to participatory landscape governance in Northern Laos: the role of Information and Communication Technologies - Watts, J.D.; Kanyasone, V.; Vongkhamsao, V. (2010)
The Landscape Mosaics Project is a global research project coordinated by the Center for International Forestry Research (CIFOR) and the World Agroforestry Centre (ICRAF) and funded by the Swiss Agency for Development Cooperation (SDC). The project examines biodiversity in tropical, forested, multifunctional landscapes in sites adjacent to protected areas. A key thematic component of its research examines the governance of landscapes, and by using a Participatory Action Research approach, the project aspires to facilitate better landscape governance through improved communication between village and landscape level actors. This article examines the initial experiences of the project in its Northern Lao site, located in Vieng Kham District, Luang Prabang Province. The authors describe how the lack of access to information communication technologies have inhibited local actors levels of participation in landscape level governance as well as affected their abilities to effectively and adaptively manage their landscape. Community radio, that provides local actors with the relevant information for more substantially participating in landscape governance as well as information useful for adaptive management, is proposed as one potential solution for improving participatory landscape governance.